2018
DOI: 10.1016/j.ultsonch.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted lipase catalyzed hydrolysis of aspirin methyl ester

Abstract: The ultrasound-assisted hydrolysis of aspirin methyl ester (AME) was investigated using immobilized Candida antarctica lipase B (CALB) (1%) in the presence of solvents like triolein, chloroform (CHCl) and dichloromethane (DCM). The effect of ultrasound and the role of water on the conversion rates have also been investigated. Proton nuclear magnetic resonance spectroscopic (H NMR) was chosen to calculate hydrolysis convertion rates. We observed that lipase-ultrasound assisted hydrolysis of AME in the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 60 publications
2
9
0
Order By: Relevance
“…After removal of the reactional mixture from the US, followed by a liquid-liquid extraction of the unreacted triacylglycerols, only free MTX was recovered in the aqueous phase. This result was expectable since recently, Chiplunkar et al reported that immobilized CALB did not hydrolyse triolein in organic medium [23]. For the short triacylglycerols used, glycerol tributyrate (C 3 ), glycerol trivalerate (C 4 ) and glycerol trihexanoate (C 5 ), after 30 min under ultrasonication, we observed the disappearance of the biphasic system formed initially, and the precipitation of a solid that turns into soluble when more water is added to the reactional flask.…”
Section: Methotrexate-acylglycerol Conjugatessupporting
confidence: 70%
“…After removal of the reactional mixture from the US, followed by a liquid-liquid extraction of the unreacted triacylglycerols, only free MTX was recovered in the aqueous phase. This result was expectable since recently, Chiplunkar et al reported that immobilized CALB did not hydrolyse triolein in organic medium [23]. For the short triacylglycerols used, glycerol tributyrate (C 3 ), glycerol trivalerate (C 4 ) and glycerol trihexanoate (C 5 ), after 30 min under ultrasonication, we observed the disappearance of the biphasic system formed initially, and the precipitation of a solid that turns into soluble when more water is added to the reactional flask.…”
Section: Methotrexate-acylglycerol Conjugatessupporting
confidence: 70%
“…The enzyme was also used to analyze the effect of water on the process of ultrasound‐assisted hydrolysis of methyl ester of acetylsalicylic acid (AME) in the presence of the CALB (1%) and in the medium of triolein, chloroform, and dichloromethane. It was demonstrated that lipase can hydrolyze AME into methyl 2‐hydroxybenzoate (methyl salicylate) that is used as a fragrance in the food and cosmetic industries as well as in the pharmaceutical industry as a topical analgesic (e.g., in liniment) …”
Section: Resultsmentioning
confidence: 99%
“…Enzymes are well‐known as catalysts, which are characterized by high selectivity and activity . In addition, the use of enzymes generally reduces the amount of reaction steps and does not require functional group protection and/or activation . In short, enzymatic processes are more environmentally friendly, cost‐effective, and sustainable .…”
Section: Introductionmentioning
confidence: 99%
“…Among all lipases, Lipase B from Candida antarctica (CALB) is widely used as biocatalyst due to its high stereo selectivity, high activity, broad substrate specificity, high thermo stability and conformational stability . However, the thermal stability of free enzymes is limited, and their tolerance to organic solvents is very low .…”
Section: Introductionmentioning
confidence: 99%